Perancangan Sistem Informasi Keuangan Boutique - Alhamidi Midi (Prodi Sistem Informasi Universitas Dharma Andalas, 2020)
The rapid development of technology makes it possible to get accurate and fast information. Boutiqe engaged in the clothing business is difficult to get accurate information on sales results due to data - sales results are still calculated manually, so Boutiqe financial information can not explain how much profit should be obtained. Weaknesses in getting accurate financial information then a computer-based information system was built that could store all sales data and produce more accurate financial reports. The information system built uses MYSQL as a data storage database.